HOW Collaborative position paper on the management of thrombocytopenia in pregnancy. (12th January 2021) - Eslick, Renee; Cutts, Briony; Merriman, Eileen; McLintock, Claire; McDonnell, Nolan; Shand, Antonia; Clarke, Lisa; Ng, Sara; Kando, Ian; Curnow, Jennifer
Abstract : Thrombocytopenia in pregnancy is a common occurrence, affecting up to 10% of women by the time of birth. These recommendations aim to provide pragmatic guidance on the investigation, diagnosis and management of thrombocytopenia in pregnancy; including safety of neuraxial anaesthesia and precautions required for birth. Management of neonatal thrombocytopenia is also addressed. The authors are clinicians representing haematology, obstetric medicine, maternal‐fetal medicine, and anaesthesia. Each author conducted a detailed literature review then worked collaboratively to produce a series of unanimous recommendations. The recommendation strength is limited by the lack of high‐quality clinical trial data, and represents level C evidence.